Comparison of resilon and gutta-percha filling materials on root canal fracture resistance following restoring with quartz fiber posts. - P Mehrvarzfar; Y Rezvani; E Jalalian (Tehran University of Medical Sciences, 2012)
Bacterial leakage and root fractures are the most important reasons of root canal treatment failure. Due to the lack of adhesion of gutta percha to the canal walls, Resilon has been introduced as a root-filling material able to bond to the root walls. Metal posts may predispose the tooth walls to oblique and vertical fracture which usually leads to tooth loss; whereas, fiber posts may reinforce the remaining tooth structure. The purpose of this study was to compare the effect of Resilon and gutta-percha on the fracture resistance of root canal following restoring with quartz fiber posts.Forty-four maxillary incisor root canals were chemo-mechanically prepared, then randomly divided into three groups: 1-Control group (n=20), 2-Experimental group (n=20) and a negative control group (n=4). Root filled teeth were restored with quartz fiber posts and composite resin cores. Four teeth with a conservative prepared access cavities and without any further post preparation were used as a negative control group. After simulating the clinical situation, specimens were loaded in the Universal Testing Machine for compressive strength test. All data were statistically analyzed by the T-test.The mean compressive strengths for group 1 was 535.8 ± 155.23 N and 645.93 ± 182.98N for group 2, which were statistically significant (p-value= 0.047).Root canals filled with Resilon were significantly more resistant than that of gutta-percha, following restoration with quartz fiber posts.